Exploring Bases of Achievement in Content and Language Integrated Assessment in a Bilingual Education Program - Morton, Tom; Nashaat‐Sobhy, Nashwa (TESOL quarterly, 2024)
This study explores the bases of achievement invoked by teachers when assessing students' work in the context of a bilingual education program where academic subjects are taught through English as a foreign language. During a professional development seminar, teachers judged samples of students' writing in response to tasks that elicited the three cognitive discourse functions (CDFs) of define, evaluate, and explore. The teachers' discourse was analyzed using specialization, a dimension of Legitimation Code Theory‐LCT (Maton, Knowledge and Knowers. Towards a realist sociology of education, 2014), a sociological framework for analyzing knowledge practices. Specialization codes provide insight into epistemic relations (knowledge) and social relations (knowers) in educational practices. The results show that within epistemic relations, there was a balance between content and language as bases of achievement. Content quality was emphasized over quantity, language form was emphasized over function, and teachers gave different weights to language depending on the quality of the content. Social relations were also invoked, though less often than epistemic relations. The results suggest that teachers' positioning of students in terms of epistemic and social relations in their assessment practices may have consequences for the equitable treatment of learners in bilingual programs.